Ibn Hazm’s Kafa’ah Relevance on Kiai’s Role Choosing His Cadre’ Spouses as Living Sharia-Based Education - Rizki, Haris Diar; Susanto, Edi; Fiqih, Haris Ilman (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
Kiai is a figure who determines who marries whom, especially if the one who marries his pesantren cadres, then the kiai has full authority to choose a life partner as the concept of kafa'ah in maintaining living sharia. In this view  of the kafa'ah, Ibn Hazm says “There is no haram for the marriage of unemployed Negroes with Banu Hashim and the wicked remain kufu with obedient women.” Likewise, noblemen also kufu with very wicked women. This type of research is literature research as part of qualitative descriptive research based on Raymond Gibbs' cognitive and communicative relevance theory approach. The results showed that cognitive relevance is that kiai see the way of thinking of their cadre partners by looking at their good understanding of religion. While the communicative relevance is, the concept of Ibn Hazm's kafa'ah to kiai who match his cadres by emphasizing moral ethics of communication to cadre pairs to maintain each other's dignity and substantial things in religion.   Keywords: Relevance Theory, Kafa’ah, Ibnu Hazm, Living Sharia